Pengaruh Promotion, Perceived Value, E- Service Quality, dan E-Trust Terhadap E-Repurchase Intention dan E-Loyalti Konsumen E-Commerce Tokopedia di Kota Banda Aceh - Ikhsan Ikhsan; Rahayu Lestari (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
The purpose of this study was to to analyze the effect of Promotion, Perceived Value E-Service Quality, E-Trust, on E-Repurchase Intention and Tokopedia Consumer E-Loyalty. The research data was analyzed using the Structural Equation Modeling (SEM) analysis method from the AMOS Version 22 statistical software. Variable measurement is done by distributing questionnaires in the form of google forms using Likert scale assessment Variable measurement is done by distributing questionnaires in the form of google forms using Likert scale assessments to 150 respondents. The sampling technique used is a non-probability sampling technique. The results of the analysis showed that the variables Promotion and Perceived Value had a significant positive effect on E-Repurchase Intention, E-Service Quality had an insignificant negative effect on E-Repurchase Intention and E-Trust had an insignificant positive effect on E-Repurchase Intention. Promotion and E-Trust variables had a significant positive effect on E-Loyalty, E-Service Quality and Perceived Value, not significant negatively on E-Loyalty. The E-Repurchase Intention variable can mediate Promotion and Perceived Value to E-Loyalty and the E-Repurchase Intention variable cannot mediate E-Service Quality and E-Trust against Tokopedia consumer E-Loyalty.